Relações laborais na Argentina logo após o kirchnerismo (2003-2015): entre a participação e o retrocesso sindical - González, Cecilia Senén (2018)
After a decade of offensive union strategies framed by a period of economic growth beginning in 2003, the arrival of a right-wing government has shifted the scenery, expanding unemployment and poverty. How do unions position themselves to resist or adapt to this new context?